Insulator aging tests with HVAC and HVDC excitation using the tracking wheel tester - Limbo, Beulah Sepo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2009.